2014
DOI: 10.1016/j.celrep.2014.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Imaging of Caspase-1 Dynamics Reveals an All-or-None Inflammasome Signaling Response

Abstract: Inflammasome-mediated caspase-1 activation is involved in cell death and the secretion of the proinflammatory cytokine interleukin-1β (IL-1β). Although the dynamics of caspase-1 activation, IL-1β secretion, and cell death have been examined with bulk assays in population-level studies, they remain poorly understood at the single-cell level. In this study, we conducted single-cell imaging using a genetic fluorescence resonance energy transfer sensor that detects caspase-1 activation. We determined that caspase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
98
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(107 citation statements)
references
References 38 publications
9
98
0
Order By: Relevance
“…2C). Recent single-cell analysis of caspase-1 dynamics revealed that dead macrophages are the main source of IL-1b secretion within cell populations (23). In contrast to MDM, U937 cells have a prolonged increase in IL-1 gene transcription in response to LPS with a gradual accumulation of cytosolic IL-1 gene products, including IL-1b (24), which explains the high IL-1b secretion despite reduced cell death.…”
Section: Resultsmentioning
confidence: 99%
“…2C). Recent single-cell analysis of caspase-1 dynamics revealed that dead macrophages are the main source of IL-1b secretion within cell populations (23). In contrast to MDM, U937 cells have a prolonged increase in IL-1 gene transcription in response to LPS with a gradual accumulation of cytosolic IL-1 gene products, including IL-1b (24), which explains the high IL-1b secretion despite reduced cell death.…”
Section: Resultsmentioning
confidence: 99%
“…Although some authors detected IL-1␤ release independent from pyroptosis (31) or pyroptosis without IL-1␤ release (32), others saw pyroptosis as the result of variable inflammasome activation (20,33). A third hypothesis claims an all-or-nothingmechanism with two states: no inflammation or pro-inflammatory cell death/pyroptosis (34). Last, a dual function of caspase-1 was suggested, controlling cell death and autoprocessing with pro-IL-1␤ cleavage through two different pathways (35), and ASC speck formation was found to be essential for release of mature IL-1␤ but not for induction of pyroptosis (36).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying pyroptosis are unknown, but appear to initially involve the appearance of caspase-1-dependent plasma membrane pores of 1.1-2.4 nm diameter [27], followed by dissipation of ionic gradients, cell swelling, and osmotic lysis. A number of studies have highlighted the temporal association of IL-1b secretion and cell lysis [15,28,29], promoting a model in which IL-1b is passively released during cell lysis. This was most recently proposed from studies in which cytokine secretion from single cells was monitored in real-time by total internal reflection fluorescence microscopy [28,29].…”
Section: Cell Deathmentioning
confidence: 99%